A revision of the genus Leontodon (Asteraceae) in the Azores based on morphological and molecular evidence - Moura, Mónica; Silva, Luís; Dias, Elisabete F.; Schaefer, Hanno; Carine, Mark (Phytotaxa, 2015)
Two endemic species of Leontodon are currently recognized in the Azores archipelago: Leontodon filii and L. rigens. However, there has been confusion regarding the application of these names and field observations and herbarium studies suggested three morphotypes in the islands. Here, we present a taxonomic revision of the Azorean endemic Leontodon species using morphological characters and new molecular data from the ITS region and from three chloroplast regions: trnQ, trnV and matK. Fifty-one quantitative and qualitative morphological characters were examined that revealed consistent differences between specimens from the western, central and eastern subarchipelagos (where, on the latter, Leontodon is restricted to São Miguel). Molecular analysis revealed two well defined monophyletic groups, one comprising accessions from São Miguel and the second comprising accessions from the western group, while central group accessions were in an unresolved polytomy. Both analyses also indicated the occurrence of hybridization with L. saxatilis, a widespread non-endemic species. Taken together, molecular and morphological data suggest the reinstatement of a third Azorean Leontodon taxon endemic to the western group. A key to the Leontodon of the Azores and descriptions of the endemic taxa are provided.